Femtosecond time-resolved photoemission electron microscopy operated at sample illumination from the rear side - Klick, Alwin; Großmann, Malte; Beewen, Maria; Bittorf, Paul; Fiutowski, Jacek; Leißner, Till; Rubahn, Horst-Günter; Reinhardt, Carsten; Elmers, Hans-Joachim; Bauer, Michael (Review of scientific instruments, 2019)
We present an advanced experimental setup for time-resolved photoemission electron microscopy (PEEM) with sub-20 fs resolution, which allows for normal incidence and highly local sample excitation with ultrashort laser pulses. The scheme makes use of a sample rear side illumination geometry that enables us to confine the sample illumination spot to a diameter as small as 6 µm. We demonstrate an operation mode in which the spatiotemporal dynamics following a highly local excitation of the sample is globally probed with a laser pulse illuminating the sample from the front side. Furthermore, we show that the scheme can also be operated in a time-resolved normal incidence two-photon PEEM mode with interferometric resolution, a technique providing a direct and intuitive real-time view onto the propagation of surface plasmon polaritons.